A 45-year sub-annual reconstruction of seawater temperature in the Bay of Brest, France, using the shell oxygen isotope composition of the bivalve Glycymeris glycymeris. (January 2020) - Featherstone, Amy M; Butler, Paul G; Schöne, Bernd R; Peharda, Melita; Thébault, Julien
A reconstruction of sea surface temperature (SST) spanning 45 years (1966–2011) was developed from δ 18 O obtained from the aragonitic shells of Glycymeris glycymeris, collected from the Bay of Brest, France. Bivalve sampling was undertaken monthly between 2014 and 2015 using a dredge. In total, 401 live specimens and 243 articulated paired valves from dead specimens were collected, of which 24 individuals were used to reconstruct SST. Temperatures determined using the palaeotemperature equation of Royer et al. compared well with observed SST during the growing season between 1998 and 2010 (Pearson's correlation: p = 0.002, r = 0.760). Furthermore, a significant negative correlation was found between the reconstructed SST and the North Atlantic Subpolar Gyre (SPG) index ( p = 0.001, r = −0.50), and a significant positive correlation was found with the East Atlantic Pattern (EAP) index when the reconstructed SST was lagged by 1 year ( p = 0.002, r = 0.46). This led to the conclusion that EAP and SPG are major influences on SSTs in the Bay of Brest. As the SPG controls air temperature in Northern Europe and the EAP controls water temperature in Southern Europe, this suggests that the Bay of Brest is an interaction area between these two climate systems. As such, this locality is interesting as the δ 18 O of the shells can be used as a proxy for both the SPG and EAP, and temperature reconstructions can provide a unique insight into how these climate systems interacted prior to the instrumental era.